PEMBERDAYAAN MASYARAKAT MELALUI PELATIHAN PEMBUATAN SABUN PADA KOMUNITAS IBU RUMAH TANGGA DI KELURAHAN WONOCOLO SURABAYA - Priskila, Onny; Ang, Suryawan; Mufida Sari, Laili (Universitas katolik Musi Charitas, 2024)
Nowadays it is very important to maintain a healthy body. The pandemic period has passed, but efforts to maintain health must be made, one of which is maintaining personal hygiene. Steps to maintain personal hygiene are washing hands, showering and washing hair. Some of these things require soap to help clean. Darma Cendika Catholic University (UKDC) together with Wonocolo Village, Surabaya City are making collaborative efforts to empower the community, generally housewives, in soap making activities. The aim of this soap making training is to develop skills, increase awareness of health and foster entrepreneurial ideas for Wonocolo sub-district housewives. The target of this activity is the Wonocolo sub-district housewives group. The training methods used include material delivery sessions and direct practice. This research involved 30 participants from community groups around Wonocolo sub-district. Before and after counseling, participants were given a questionnaire, the average result before counseling was 4 and after counseling was 9.2. These results indicate that the material delivered and the soap making training provided were effective in increasing participants' knowledge. It is hoped that this community service activity will have a positive impact on housewives in Wonocolo sub-district and that participants will be able to develop new skills in making soap.